PENGARUH PELAKSANAAN REKRUTMEN TERHADAP KINERJA KARYAWAN PT. RIAUJAYA CEMERLANG PEKANBARU - Apriani "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: the current labor Problems are complex because of the increasingly rapid technological adanyaperkembangan and the presence of pertumbuhanpersaingan. The main challenge is how to choose, manage karyawandengan effective and eliminate practices that are not selective, i.e. by means of precision recruitment activities, it will look darihasil working assessment after the workers carrying out tasks anyway for a certain period.In environmental conditions above a Manager is required to constantly develop new ways to be able to select and retain high-quality employees are necessary to keep the company mampubersaing.To form a quality workforce is the need to determine the qualifications of the labour force is needed and put them padajabatan the right, so that the objectives of the company will be achieved. To achieve the objectives of the company then needed a baikuntuk workforce planning of each Division or Department within the company.Existing problems on the company's brilliant riaujaya that the high number of incoming outgoing employees, this makes the company continues to conduct recruitment to get employees who are truly loyal and have a good performance against the company.Research objectives to find out and analyse the implementation of the recruitment of employees of PT.Riaujaya Brilliant Soweto, To Know The Performance Of The Employees Of Pt. Riaujaya Brilliant Soweto, To Know How The Implementation Of Recruitment Against The Performance Of The Employees Of Pt. Riaujaya Brilliant PekanbaruThe results showed good results, meaning that with the implementation of proper recruitment will increase the good performance at the company.Keywords: Recruitment, Employee Performance,